Exploring motivations and barriers in prostate cancer screening: lessons from a volunteer-based MRI screening study - Světlák, Miroslav; Standara, Michal; Malatincová, Tatiana; Staník, Michal; Miklánek, David; Hejcmanová, Kateřina; Pacal, Miloš; Hrabec, Roman; Ngo, Ondřej; Hejduk, Karel; Křístek, Jan; Uher, Michal; et al. (Frontiers in Public Health, 2025)
BackgroundProstate cancer remains a significant public health challenge, an early detection with prostate-specific antigen (PSA) testing and biparametric MRI (bpMRI) can improve outcomes. However, participation hinges on motivational, psychological, and logistical factors. This study examines the motivational profile of men in the ProstaPilot study to guide strategies to increase uptake of state-of-the-art prostate cancer screening programs.MethodsThe ProstaPilot study enrolled 423 men who underwent both PSA testing and bpMRI of the prostate. Positive results (PSA ≥ 3 μg/L or PI-RADS 4–5 lesions) were referred for further urological examination and biopsy. Using an exploratory correlational design, 360 participants completed a detailed questionnaire. Motivational factors were extracted via Principal Component Analysis (PCA) with Oblimin rotation. Perceptions of prostate cancer risk, severity, and prevention were rated on 1–10 scales (10 = most positive).ResultsPCA identified four motivational factors explaining 55.6% of variance: (1) concerns about screening (e.g., unnecessary surgery, loss of control); (2) perceived benefits of early detection; (3) social motivation (e.g., contributing to research, role modeling); and (4) barriers (e.g., logistics, embarrassment). Over half (51.1%) had not considered screening before ProstaPilot; others decided over varying timeframes. Participants showed high awareness of prostate cancer and valued early detection, rating screening effectiveness 9.55 ± 0.98 and trust in healthcare professionals 9.6 ± 1.0. Social/familial influences were moderate. Satisfaction was high: likelihood to recommend 9.45 ± 1.22; confidence in continuing participation 9.9 ± 0.39.ConclusionHighly motivated participants were marked by strong knowledge of prostate cancer screening, trust in healthcare providers, supportive social context, and high personal commitment. These findings support personalized, socially supportive, educational strategies to increase uptake of state-of-the-art screening.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT05603351.